The evolving landscape of agricultural biodiversity conservation: Community-based Biodiversity Management (CBM): A landscape approach to the conservation of agricultural biodiversity cultivated on fifteen years of experiences in Begnas, Nepal - Sthapit, S.; Mijatović, Dunja; Paudel, I.; Neupane, S. (Local Initiatives for Biodiversity, Research and Development, Nepal, 2014)
Community-based Biodiversity Management (CBM) is an emerging landscape approach to agricultural biodiversity conservation. CBM seeks to encourage the custodianship of land and agricultural biodiversity as a means for improving livelihoods of local communities. Local Initiatives for Biodiversity, Research and Development (LI-BIRD), in collaboration with national and international research organizations, has been developing CBM through participatory action research projects in 15 districts in Nepal. One compelling example of CBM is the restoration of the Rupa lake watershed in Begnas, in the Lekhnath Municipality in Kaski district of Nepal.